Assessing real-world implementability of a multimodal group-based tele-prehabilitation program in cancer care: a pragmatic feasibility study - Piché, Alexia; Santa Mina, Daniel; Lambert, Sylvie; Doré, Isabelle (Frontiers in Oncology, 2023)
Multimodal prehabilitation is intended to optimize a patient’s mental and physical health prior to surgery. Most multimodal prehabilitation interventions are delivered on a one-on-one format, which may limit benefits associated with social interactions that can be achieved in a group context, and are delivered in-person, which may limit the accessibility. The purpose of this study was to develop a group-based, multimodal, tele-prehabilitation intervention for individuals diagnosed with cancer (iACTIF) and assess its implementability in a “real-world” clinical setting by measuring feasibility, acceptability, fidelity, and preliminary effects. A prospective, single-group, pragmatic feasibility study was conducted with assessments at baseline, pre-surgery and 12-weeks post-surgery. iACTIF consisted of three 90-minute live videoconference sessions per week, including exercise and educational components. Descriptive statistics were used to document feasibility, acceptability, and fidelity indicators. Paired t-test, Wilcoxon and Cohen’s D tests were conducted to assess changes in health-related outcomes. Twenty-five participants (mean age  SD= 60.2  14.0) were recruited. The feasibility assessment revealed a low referral rate (31.4%), a high study retention (98%) and program attendance [session attended/ possible session] (70.2 %), with a prehabilitation window of 32.7 days (SD= 20.9, median= 28). Acceptability was high (84-100%) according to satisfaction, utility and safety, delivery modality, and intention to continue physical activity and to recommend iACTIF to a relative. Pre-post intervention assessments suggest positive changes on physical functional capacity based on the 2-minute step test (mean difference= +18.9 steps, p=0.005), the 30-second sit-to-stand (mean difference= +1.1 repetition, p=0.011), and volume of moderate intensity physical activity per week (mean difference= +104.8 minutes, p<0.001). Fidelity was supported by conformity and coherence, with only minimal adjustments required to meet participants’ needs. iACTIF implementability in a “real-world” clinical setting is promising and preliminary outcomes suggest moderate benefits on physical health and small increased in mental health indicators.